Perbedaan Kinerja Keuangan Pemerintah Daerah Antara Daerah Induk Dan Daerah Otonom Baru Setelah Pemekaran - Aprilia, Elma Sherly; , Dr. Triyono, S.E., M.Si (2017)
This study aims to obtain empirical evidence about the performance differences between local government finances and new autonomous regions in the period of one year, two years, three years, four years and five years after separation in improving the quality of services as well as wealth distribution. The variable used is the ratio of the efficiency, independence ratio, the ratio of expenditure management, the ratio of the degree of decentralization and the ratio of operating expenditure. Testing data include descriptive statistics and normality test to determine the different types of test used for hypothesis testing. hypothesis testing that distribution normal used T-test and that is not normal distribution using Mann-whitney. Results of t-test and Mann-Whitney test show that the region whose seperated in 2007, in the independence ratio, management of the shopping area ratio, and operating expenses ratio show that there aren't differences between the parent and the new autonomous regions after separation but in the efficiency ratio and degree of decentralization ratio show that there are differences between the parent and new autonomous region after separation. The region whose seperated in 2008, in the efficiency ratio, management of the shopping area ratio, degree of decentralization ratio and the operating expenses ratio show that there aren't differences between the parent and the new autonomous regions after separation, different from independence ratio show that there are differences between the parent and new autonomous region after separation.